Diagnostic Algorithm for Joint Pain in Patients with Inflammatory Bowel Disorders - A. I. Dolgushina; G. M. Khusainova; O. B. Nesmeyanova; N. V. Kirsh; O. V. Solovieva; E. A. Bogdanova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. An algorithm development for joint pain differential diagnosis in patients with inflammatory bowel disorders (IBD) and its validation in clinical practice.Materials and methods. A total of 349 IBD patients hospitalised for gastroenterological complaints at the Chelyabinsk Regional Clinical Hospital during 2017–2020 have been examined.Results. Upon survey, 97 (27.8%) IBD patients complained of joint pain. Ulcerative colitis (UC) predominated (79 patients; 81.4%), Crohn’s disease (CD) had a 18.6% incidence. In survey, 27% UC and 32.1% CD patients reported joint pain (p = 0.26). Among IBD patients, 52.6% had mechanical, and 47.4% — inflammatory pain. The inflammatory back pain (IBP) rate in survey cohort was 23.7%. Use of a diagnostic algorithm allowed concomitant rheumatic disease detection in 7 (7.2%) patients from the IBD–joint pain cohort: 2 patients were diagnosed with psoriatic spondyloarthritis, 2 — rheumatoid arthritis, 1 — gout and 2 — with ankylosing spondylitis. IBD-associated arthritis was diagnosed in 41 (42.3%) cases, osteoarthritis — in 38 (39.2%) IBD patients with joint pain, arthralgia with no objective inflammation, impaired joint function or lesions in X-ray and/or ultrasound — in 13 (13.4%) patients.Conclusion. Joint pain complaints are common in IBD patients and require a multispecialty rheumatologists-involving approach to proceed with differential diagnosis and opting for treatment tactics. A clinically verified algorithm coupled with laboratory tests and instrumental imaging facilitates diagnosis and optimal therapy selection in IBD patients with complaints of joint pain.